Das Lab und seine Wirkung auf das Casein der Milch - Hs. Nitschmann; R. Beeby (CHIMIA)
Rennin releases from k-casein a glyco-macropeptide which is identical with the one previously obtained from α-casein and from whole casein. All preparations have the same quantitative amino-acid composition. As k-casein has been recognised to be the protective colloid of the calcium-caseinate micelles in milk, this fact supports the assumption that the splitting off of this glyco-macropeptide is the decisive reaction in the rennet-clotting of milk.